Perceptions of dental undergraduates in India of a clinical induction program - Arati Panchbhai (Journal of Educational Evaluation for Health Professions, 2015)
This study aimed to investigate undergraduate students’ perceptions of the clinical induction program for dental undergraduates conducted at the DMIMS Deemed University, Sawangi-Meghe, India. Seventy-four third-year dental students who entered the clinical phase of the dental program in 2012 and attended all sessions of the clinical induction program were enrolled in this study. The students’ perceptions of the clinical induction program were assessed through a Likert-scale questionnaire, focus group discussions, and individual interviews. Seventy-two students (97.3%) responded positively about the program, evaluating it as successful and making a few suggestions. Fifty-four students (73.0%) stated that the clinical tours and visits to the departments were the best feature of the program. Nine students (12.2%) suggested that the program should include interaction with their immediate seniors and that interactive activities should be included in the program. The induction program may help students become acclimated during the first few days of being introduced into the clinical phase of their education. It is crucial to ensure that students do not develop a negative attitude towards their educational program by facilitating their smooth transition to the clinical phase.